Prevalence of SARS-CoV-2 Positivity in Pediatric Surgical Patients Amid the First Wave of the COVID-19 Pandemic in New York City. Issue 1 (22nd January 2022) - Price, Jerri C.; Lee, Jennifer J.; Ing, Caleb; Li, Guohua; Narula, Jacquelin; Clark, Mary K.; Stylianos, Steven; Whittington, Robert A.; Levy, Richard J.; Sun, Lena S.
Abstract : Introduction: New York State implemented an 11-week elective surgery ban in response to the coronavirus disease-2019 (COVID-19) pandemic, during which pediatric patients from the 10 New York Presbyterian network hospitals requiring urgent or emergent surgical procedures were cared for at Morgan Stanley Children's Hospital (MSCH). Materials and Methods: Data was abstracted from the electronic medical record of all patients aged 0 to 20 years who had surgery at MSCH from March 23, 2020 to June 7, 2020. Comparative analysis of demographic and clinical data elements between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-positive and negative cohorts was conducted using the Fisher exact tests. Results: A total of 505 surgical procedures were performed in 451 patients, with 32 procedures (6.3%) performed in 21 SARS-CoV-2-positive children. The prevalence of SARS-CoV-2 positivity in Medicaid beneficiaries was more than twice the prevalence in commercially insured (6.8% vs. 2.6%, P =0.04) children. SARS-CoV-2-positive patients were more likely to undergo multiple surgical procedures (23.8% vs. 7.2%, P =0.02), and to have higher American Society of Anesthesiologists (ASA) class designations (69.8% III to V vs. 47.4% I to II, P =0.03). There was no significant difference in the prevalence of SARS-CoV-2 positivity across sex, age, race, or ethnicity groups, or in emergent case status or surgical procedure type. Thirty-day mortality rate was <0.1% overall, with no deaths in the SARS-CoV-2-positive group. Conclusions: During the first wave of the COVID-19 pandemic in New York City, we found a higher prevalence of SARS-CoV-2 positivity in urgent/emergent pediatric surgical patients compared with other institutions in the United States. SARS-CoV-2-positive patients were more likely to be Medicaid beneficiaries, were clinically more complex, and had more surgical procedures.